Well-being, Malaise and Quality of Work Life Management - Ferreira, Mário César (2022)
The issue of Quality of Work Life (QWL) has assumed social and corporate relevance due to the worsening of harmful indicators for the health and safety of workers and the scope of the organizational mission. The research aimed to highlight the structuring representations of well-being and malaise at work by servants of a public organization aiming to contribute to the sustainable management of QWL. A total of 1,110 civil servants of an executive branch of the Federal District participated in the survey. Data were collected based on two open questions from the qualitative part of the Quality of Work Life Assessment Inventory (IA_QVT) and were analyzed using the IRaMuTeQ application. The results pointed to three discourse structuring thematic nuclei for work well-being (having a good relationship with colleagues, doing a job you like and feeling useful to society) and malaise at work (work overload, lack of recognition and time pressure and rework). Therefore, sustainable management of quality of working life must be anchored in people management practices that foster professional development, the alignment between tasks, roles and organizational mission, highlighting the social contributions, the recognition of the worker by his/her superiors, peers and society, and the review of work organization, focusing on the reassessment of work processes, distribution of demands and ways of setting and demanding goals.